From laboratory to field: OsNRAMP5-knockdown rice is a promising candidate for Cd phytoremediation in paddy fields. - Ryuichi Takahashi (Public Library of Science (PLoS), 2014)
Previously, we reported that OsNRAMP5 functions as a manganese, iron, and cadmium (Cd) transporter. The shoot Cd content in OsNRAMP5 RNAi plants was higher than that in wild-type (WT) plants, whereas the total Cd content (roots plus shoots) was lower. For efficient Cd phytoremediation, we produced OsNRAMP5 RNAi plants using the natural high Cd-accumulating cultivar Anjana Dhan (A5i). Using a positron-emitting tracer imaging system, we assessed the time-course of Cd absorption and accumulation in A5i plants. Enhanced 107Cd translocation from the roots to the shoots was observed in A5i plants. To evaluate the phytoremediation capability of A5i plants, we performed a field experiment in a Cd-contaminated paddy field. The biomass of the A5i plants was unchanged by the suppression of OsNRAMP5 expression; the A5i plants accumulated twice as much Cd in their shoots as WT plants. Thus, A5i plants could be used for rapid Cd extraction and the efficient phytoremediation of Cd from paddy fields, leading to safer food production.